Bus booking system (BBS) - Siti Nor Atiqah, Mat Zin (2018)
The Bus Booking System (BBS) is a web-based application that is developed to improve the existing systems which is used by bus passengers to book the bus. The development of this system is to help bus passengers to book the bus online and also help the administrator to store the booking information in the database. The proposed system helps to overcome the problems of manual bus booking that are inconvenient and required more time and energy. This project focuses on bus passengers at UMP Gambang which covers students from different faculty, course, year of study and their destinations.This system is written using HTML, CSS, PHP and JavaScript programming language. Rapid application development (RAD) is a methodology used in development of this application. The RAD consists of four phases of requirements planning, user design, construction, and cutover/transition. All these phases are guidelines in developing this system. After development of the system, user will be given user acceptance test (UAT) to ensure every functions in this system work properly. The advantages of this system is that BBS replaced the previous version of manual bus booking by enabling users to make online bus booking that can be made anywhere and anytime. By using BBS, the management of the booking process will be more organised as all the information and data will be inserted into the system and stored in the database. Last but not least, encouragement of human-computer interaction. Rather than human-to-human interaction, the online booking (BBS) will encourage users to interact with computers.